Non-Consensuality Pathologised: Analysing non-consensuality as a determiner for paraphilic disorders - Theron, Shirah (The Stellenbosch Socratic Journal, 2022)
The fifth text-revised iteration of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5-TR) defines paraphilia as "any intense and persistent sexual interest other than sexual interest in genital stimulation or preparatory fondling with phenotypically normal, physically mature, consenting human partners". Paraphilic disorders specifically denote a paraphilia that is "currently causing distress or impairment to the individual or a paraphilia whose satisfaction has entailed personal harm, or risk of harm, to others". A diagnosis of paraphilic disorder either demands the personal distress and/or impairment of function that is caused by the atypical sexual urges and fantasies to be present, or the status of non-consent of the other person that these sexual fantasies and urges are directed towards when acted upon by the patient. This paper discusses how consent not only becomes the standard for permissible and legal sexual activity with other persons, but also, when the diagnostic criteria are taken at face-value, for sexual pathology in the DSM-5-TR when the patient acts on their sexual urges. After a close investigation of various possible interpretations of the element of non-consensuality in the diagnostic criteria for paraphilic disorders, this paper concludes that the DSM-5-TR does not offer a clarifying explanation on how mental health professionals should understand its approach to diagnosing paraphilic disorders, leaving us with an ambiguous, unclear and unsettled conceptualisation of what it would mean to fulfil its diagnostic criteria.